Improving Information Technology When Using Terms Related to the Tourism Industry - Vafokulovna, Nishanova Xafiza (European Journal of Life Safety and Stability (2660-9630), 2022)
The purpose of this article is to improve the efficiency of information technology in the development of tourism in our country, and it addresses the issues of developing information and communication technologies in the creation of tourism products, as well as the tasks and measures that must be implemented.